Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

L’accès aux soins de santé pour les communautés minoritaires de langue officielle : fondements juridiques, initiatives actuelles et perspectives d’avenir - Bélanger, Mauril; Comité permanent des langues officielles (Gouvernement du Canada, Chambre des communes, 2003)

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)
fs-ref-orig: Commissariat aux langues officielles. (2019). L’offre active une culture de respect, une culture d’excellence : dépliant [infographie]. fs-code-orig: Commissariat aux langues officielles-2019

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)
fs-ref-orig: Commissariat aux langues officielles. (2017). L’offre active une culture de respect, une culture d’excellence : guide complet. fs-code-orig: Commissariat aux langues officielles-2017.

Société, langue et santé : les barrières à l'accès aux services de santé pour les communautés francophones minoritaires - Consortium national de formation en santé (Santé Canada, 2008)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Le démarrage d'un programme national de recherche sur la santé des communautés francophones minoritaires - une initiative du Consortium national de formation en santé - Desbiens, Francine (Reflets, 2005)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Statistique Canada, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Statistics Canada, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

De l’émergence à la consolidation. L’état de santé des francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Nkolo, Christiane; Boudreau, Jonthan (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)
fs-ref-orig: Gagnon-Arpin, I. (2011). Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa]. uO Research. http://dx.doi.org/10.20381/ruor-4657 fs-code-orig: Gagnon-Arpin-2011c

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A. et Bélanger, M. (2014). Accès et utilisation des services de santé en langue minoritaire. Dans R. Landry (dir.), La vie dans une langue officielle minoritaire au Canada (p. 195-221). Presses de l’Université Laval. fs-code-orig: Gagnon-Arpin-2014b

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A., & Bélanger, M. (2014). Access and use of health care services in the minority language. In R. Landry (Ed.), Life within an official language minority in Canada (pp. 177-198). Canadian institute for research on Linguistic Minorities. fs-code-orig: Gagnon-Arpin-2014a

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance
The standard can be bought from this web page.

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.
Ce document qui décrit la norme créé en 2018 n'est plus disponible. La norme a été révisée en 2022 et c'est cette révision de 2022 qui peut être acheté sur la page web suivante: https://healthstandards.org/fr/standard/acces-aux-services-de-sante-et-aux-services-sociaux-dans-les-langues-officielles-confirmation/

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité
La norme peut être achetée à partir de cette page web.

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A. et Scott, M. (2022). Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux. Université d'Ottawa et Institut de recherche Bruyère. fs-code-orig: Hsu-2022a

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A., & Scott, M. (2022). Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Bruyère Research Institut. fs-code-orig: Hsu-2022b

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)
fs-ref-orig: Ménard, A., Scott, M. et Hsu, A. T. (2022). Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Institut de recherche Bruyère. fs-code-orig: Ménard-2022

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

L’offre active de services en français : généalogie d’un outil de politique publique - Normand, Martin (Francophonies d'Amérique, 2019)
L’offre active de services en français est un principe qui s’est rapidement imposé dans le discours des principaux intervenants dans le domaine de la promotion et de la protection des langues officielles et de la dualité linguistique au Canada. Elle a été intégrée à des politiques, à des règlements et à des lois au palier fédéral et dans plusieurs provinces canadiennes. Plusieurs travaux ont été consacrés aux aspects liés à la mise en oeuvre du principe. Cet article va au-delà de ces contributions pour retracer l’histoire de l’offre active. Il répond à deux questions : 1) quelle est l’origine de l’offre active ? et 2) quels sont les principaux jalons dans son évolution et sa diffusion ? L’hypothèse est que les représentations initiales de l’offre active n’étaient pas que techniques ou formalistes et qu’elles se sont effritées avec le temps. La recherche repose essentiellement sur des sources primaires et secondaires, qui nous ont permis de reculer jusqu’au moment où le principe semble avoir émergé. Le texte s’organise autour de trois périodes : la conceptualisation, l’institutionnalisation et la diffusion de l’offre active.

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Directory of innovative practices in health and social services in official language minority contexts - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)
fs-ref-orig: Société santé en français. (2012). Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée. fs-code-orig: Société Santé en français-2014

Sensibilisation, structuration et consolidation en santé en français : 10 ans d’action - Société Santé en français (Reflets, 2014)

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Désinstitutionalisation psychiatrique en Acadie, en Ontario francophone et au Québec, 1930-2013 - Thifault, Marie-Claude; Dorvil, Henri (Presses de l’Université du Québec, 2015)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.